ASSESSMENT OF HEPATITIS B VACCINATION STATUS IN DOCTORS OF SERVICES HOSPITAL, LAHORE - Usmani, Rabia Arshed; Rana, Maaz Suhail; Wazir, Muhammad Saleem; Sarwer, Huda; Fazli, Huda; Pervaiz, Muhammad Ali; Tahir, Irum; Sajjad, Rabbiya (Journal of Ayub Medical College Abbottabad, 2010)
Background: Hepatitis B is the most common serious infection of the liver and can lead to premature death from liver cancer or liver failure. Of the two billion people who have been infected with Hepatitis B virus, more than 350 million have chronic infection. The objectives of this study were to assess the Hepatitis B vaccination status, reasons for non-compliance and the risk of exposure to doctors at a tertiary care hospital. Methods: Three hundred and twenty-two doctors were selected from the various departments of the hospital by simple random sampling. They were given a self-administered questionnaire after taking verbal consent. Some doctors refused to fill-in the questionnaire while some others were on leave during the time of study and the remaining 215 doctors responded to the questionnaire. Results: A total of 215 doctors, (age range 22-59 years) responded to the questionnaire. Amongst them 11.6% had not received even a single dose of Hepatitis B vaccine while 14.4% had not completed the required course of vaccination. Most common reason cited by doctors for nonimmunisation was that they had not thought about it. Consultants were more likely of the other doctors to have received completed vaccination (83.9% versus 69.9%) (p<0.05). They were also significantly more likely to know their antibody titre after completing vaccination. Needle stick injuries were common. One hundred and forty-five doctors in the study admitted having received at least one needle prick/sharp injury. Of them, 51.6% had received a needle prick/sharp injury more than once. Conclusion: Despite the availability of an effective vaccine in the market doctors continue to remain non-vaccinated. It is the lack of awareness and carelessness on part of doctors coupled with the negligence of the risk that has led them being incompletely vaccinated. There is a need to ensure that every doctor is completely vaccinated against Hepatitis B before he/she enters professional practice. Keywords: vaccination, Hepatitis B, medical staff, professional hazard, needle prick injury